2012
DOI: 10.1002/nau.21216
|View full text |Cite
|
Sign up to set email alerts
|

Under the tip of the iceberg: Psychological factors in incontinence

Abstract: Cognitive barriers and safety behaviors explain some of the atypical psychological patterns seen in patients with UI. Future research should be oriented to design multimodal interventions and assess their impact on health outcomes. Whenever possible, the assessment of emotional, cognitive, and behavioral responses in individuals with UI could improve the management of this condition. Cognitive-behavioral therapy should be recommended to certain patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 14 publications
0
23
0
1
Order By: Relevance
“…This result seems plausible given that UI has been linked to a range of ‘safety-seeking behaviors’ that are used to manage the condition and its effects, such as avoiding contact with others, intimacy and activities outside the home [45] that might all lead to social isolation among those with UI and give rise to feelings of loneliness. Moreover, the results from the analyses examining UI severity also seem to support this idea as activity limitations were strongly associated with loneliness in the whole sample and when the analysis was restricted to those with UI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result seems plausible given that UI has been linked to a range of ‘safety-seeking behaviors’ that are used to manage the condition and its effects, such as avoiding contact with others, intimacy and activities outside the home [45] that might all lead to social isolation among those with UI and give rise to feelings of loneliness. Moreover, the results from the analyses examining UI severity also seem to support this idea as activity limitations were strongly associated with loneliness in the whole sample and when the analysis was restricted to those with UI.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a recent study has reported that a lower sense of mastery significantly contributes to the association between depression and (emotional) loneliness [27] while other research has indicated that UI is associated with a lower sense of mastery [46] and that there is an association between a poor sense of mastery and depression in those with UI [47]. One of the safety-seeking behaviors among those with UI – inquiring frequently if he or she smells [45] – might also be a factor that links depression and loneliness, as a more general connection has been shown to exist between seeking reassurance excessively and both depression and interpersonal rejection [48]. …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that women with UI, and particularly those with severe symptoms, are embarrassed by their condition and that lifestyle changes due to UI (e.g., avoiding social activities) may adversely impact mental health [3]. The association may also be bi-directional.…”
Section: Discussionmentioning
confidence: 99%
“…In several large studies of U.S. women aged 50 years and older, approximately one-third to two-thirds of women reported UI [1,2]. The impact of UI on quality of life can be substantial, including causing embarrassment and shame which may lead to harmful coping behaviors such as decreased participation in social and physical activities [3]. In addition, there is evidence that the prevalence of depression is higher among women with UI compared with those without UI [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety and depression are both consistently associated with UUI. In particular, the need to always be near toilet facilities can severely restrict a persons movements outside their home, with its impact on both work and social interaction and is a contributory factor to anxiety or depression . Work productivity can also be impaired by UUI, as demonstrated in the EpiLUTS study whilst the EPIC study found that OAB sufferers are significantly more likely to be unemployed compared to controls (42.0% vs 33.6%) .…”
mentioning
confidence: 99%